Behavioral phenotypes of mice lacking purinergic P2X4 receptors in acute and chronic pain assays - Tozaki-Saitoh Hidetoshi; Nagata Kenichiro; Inoue Tomoyuki; Kuboyama Kazuya; Tsuda Makoto; Inoue Kazuhide (SAGE Publishing, 2009)
Abstract A growing body of evidence indicates that P2X receptors (P2XRs), a family of ligand-gated cation channels activated by extracellular ATP, play an important role in pain signaling. In contrast to the role of the P2X3R subtype that has been extensively studied, the precise roles of others among the seven P2XR subtypes (P2X1R-P2X7R) remain to be determined because of a lack of sufficiently powerful tools to specifically block P2XR signaling in vivo. In the present study, we investigated the behavioral phenotypes of a line of mice in which the p2rx4 gene was disrupted in a series of acute and chronic pain assays. While p2rx4-/- mice showed no major defects in pain responses evoked by acute noxious stimuli and local tissue damage or in motor function as compared with wild-type mice, these mice displayed reduced pain responses in two models of chronic pain (inflammatory and neuropathic pain). In a model of chronic inflammatory pain developed by intraplantar injection of complete Freund's adjuvant (CFA), p2rx4-/- mice exhibited attenuations of pain hypersensitivity to innocuous mechanical stimuli (tactile allodynia) and also of the CFA-induced swelling of the hindpaw. A most striking phenotype was observed in a test of neuropathic pain: tactile allodynia caused by an injury to spinal nerve was markedly blunted in p2rx4-/- mice. By contrast, pain hypersensitivity to a cold stimulus (cold allodynia) after the injury was comparable in wild-type and p2rx4-/- mice. Together, these findings reveal a predominant contribution of P2X4R to nerve injury-induced tactile allodynia and, to the lesser extent, peripheral inflammation. Loss of P2X4R produced no defects in acute physiological pain or tissue damaged-induced pain, highlighting the possibility of a therapeutic benefit of blocking P2X4R in the treatment of chronic pain, especially tactile allodynia after nerve injury.